Prevention of fifth metatarsal bone stress fracture in youth Japanese soccer players - Yoshitomo, S.; Nagao, M.; Kobayashi, Y.; Kobayashi, K.; Wakayama, T.; Ikeda, H. (British Journal of Sports Medicine, 2021)
Background The stress fracture of the fifth metatarsal bone (5MT) frequently occurs in youth soccer players in Japan, and it is very important issue to prevent this fracture.